Political Instability Explains Political Economy of Pakistan: A Retrospective Analysis - Taha, S. M. (International Journal of Economics, Business and Management Studies, 2012)
Pakistan is among few countries of the world where political instability badly damaged the economic growth despite tremendous resources. This paper focuses on the interplay of political decisions and national economic growth in Pakistan. The primary aim of the study is to give a discursive historical analysis of political instability in Pakistan and how it worsened the economic growth. The study finds that the economic mismanagement is the result of lack of vision, will and capability of the political leadership in Pakistan. Another conclusion this study draws that the military regimes performed better than civilian governments. The study conclude that nature of Pakistani federation and its tug of war for power with federating units lead to uneven development in Pakistan which messed up the commercial cities of Pakistan because of population influx.